2022
DOI: 10.22467/jwmr.2021.01907
|View full text |Cite
|
Sign up to set email alerts
|

Effective Single-Use Portable Negative Pressure Therapy Used in Acute Morel-Lavallee Lesions: A Case Report

Abstract: Morel-Lavallee (ML) lesions are closed degloving injuries characterized by post-traumatic fluid collection and nonspecific clinical features, such as pain and soft, fluctuant appearance. Though often misdiagnosed, they can be identified by analyzing the patient’s clinical trauma history, fluid collection in a typical location, and imaging findings. After diagnosis, various treatments can be attempted, from conservative treatment to surgery, depending on the condition of the wound. Acute ML lesions can be treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…[20,21,[23][24][25][26][27] The single-use disposable portable NPWT was used in one case for acute sacral MLL. [9] The single-use ultraportable NPWT device delivers negative pressure at -80 mmHg in a continuous pattern and is a small, canister-free device that is easy to operate and less uncomfortable in daily life. [28] Limitations to this study need to be considered.…”
Section: Open Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21,[23][24][25][26][27] The single-use disposable portable NPWT was used in one case for acute sacral MLL. [9] The single-use ultraportable NPWT device delivers negative pressure at -80 mmHg in a continuous pattern and is a small, canister-free device that is easy to operate and less uncomfortable in daily life. [28] Limitations to this study need to be considered.…”
Section: Open Surgerymentioning
confidence: 99%
“…Although many studies have reported the efficacy of various treatment regimens, such as conservative treatment, percutaneous aspiration, sclerotherapy, minimally invasive surgery, open surgery, or negative pressure wound therapy (NPWT), high-quality evidence remains lacking. [5,[7][8][9][10] To the best of our knowledge, the number of cases of MLL treated with portable NPWT is very small and no reviews have been reported.…”
Section: Introductionmentioning
confidence: 99%